The Politics, Sociology and Economics of Education
XII, 294 p.
Keywords: This book uses international and interdisciplinary approaches to the comparative study of education in its political, sociological, and economic contexts. Major topics include critical theory, hegemony, postmodernism, oppression, disabilities, emancipation, corporatism, meritocracy, democracy, socialization, reproduction, pluralism, inequality, social analysis, postindustrialism, predatory culture, pragmatism, and 'subversion'. Educators from the US, UK, Canada, Netherlands, FRG, Israel, and Sweden survey the current educational scene in the US and Western Europe, major policy debates, and possible solutions for current public policy dilemmas.